A Dendritic PolymerBased Nanosystem Mediates Drug Penetration and Irreversible Endoplasmic Reticulum Stresses in Tumor via Neighboring Effect - Zheng,X; Pan,D; Zhu,G; Zhang,L; Bhamra,A; Chen,R; Zhang,H; Gong,Q; Gu,Z; Luo,K (Advanced Materials, 2022)
Abstract Nanoparticles (NPs)based cancer therapeutics are generally impeded by poor drug penetration into solid tumors due to their dense tumor extracellular matrix (ECM). Herein, pH/redoxresponsive dendritic polymerbased NPs are developed to amplify the neighboring effect for improving drug penetration and driving cell apoptosis via combination therapy. Pyropheophorbide a (Ppa) is conjugated with PEGylated dendritic peptides via disulfide bonds and doxorubicin (DOX) encapsulated in the conjugate to construct dualresponsive NPs, PDPP@D. Delayed released DOX and Ppa from PDPP@D exert their combination therapeutic effect to induce cell apoptosis, and then they are liberated out of dying cells to amplify the neighboring effect, resulting in their diffusion through the dense ECM and penetration into solid tumors. Transcriptome studies reveal that PDPP@D leads to irreversible stress on the endoplasmic reticulum and inhibits cell protection through blocking the IRE1dependent survival pathway and unleashing the DR5mediated caspase activity to promote cell death. The strategy of amplifying the neighboring effect of NPs through combination therapy may offer great potential in enhancing drug penetration and eradicating solid tumors.